2008
DOI: 10.1172/jci31350
|View full text |Cite
|
Sign up to set email alerts
|

KBMA Listeria monocytogenes is an effective vector for DC-mediated induction of antitumor immunity

Abstract: Together, our data demonstrate that KBMA L. monocytogenes may be a powerful platform that can both deliver recombinant antigen to DCs for presentation and provide a potent DC-maturation stimulus, making it a potential cancer vaccine candidate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 52 publications
(98 reference statements)
1
22
0
Order By: Relevance
“…Lastly, mimotopes may be identified by screening of peptides with antibodies, enabling immunization with epitopes that are difficult to create artificially, which is particularly important for vaccination against cancer (125). A special case of vectors is represented by killed but metabolically active Listeria bacteria (10,107). These bacteria can still be taken up by dendritic cells, carrying with them foreign genes that express proteins in those professional antigen-processing cells.…”
Section: Miscellaneous Strategiesmentioning
confidence: 99%
“…Lastly, mimotopes may be identified by screening of peptides with antibodies, enabling immunization with epitopes that are difficult to create artificially, which is particularly important for vaccination against cancer (125). A special case of vectors is represented by killed but metabolically active Listeria bacteria (10,107). These bacteria can still be taken up by dendritic cells, carrying with them foreign genes that express proteins in those professional antigen-processing cells.…”
Section: Miscellaneous Strategiesmentioning
confidence: 99%
“…In the past decade, a large body of studies have demonstrated that a live-attenuated LM vector can induce both CD4 þ and CD8 þ T-cell responses without causing harmful toxicity when used in an animal model or clinical study (Shedlock et al, 2003;Souders et al, 2006;Skoberne et al, 2008;Seavey et al, 2009;Wallecha et al, 2009). It is widely understood that Listeria is rapidly taken-up by immune cells such as dendritic cells and macrophages upon entering the host.…”
Section: Discussionmentioning
confidence: 99%
“…As an intracellular parasite, LM has direct access to the cytoplasm of antigen-presenting cells such as macrophages and dendritic cells. The antigenpresenting cells infected by LM, which carries foreign antigen genes, present foreign antigens with both major histocompatibility complex (MHC) class I and MHC class II molecules efficiently, thus inducing both a CD8 þ and CD4 þ antigen-specific T-cell response (Shedlock et al, 2003;Souders et al, 2006;Skoberne et al, 2008). Another important feature of LM is the hemolytic activity of listeriolysin O, which has a critical role in allowing the bacterium to be effectively targeted by the cellular immune system (Gedde et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, production/secretion, MHC processing, and presentation of vector immunogens in APC via the intravenous or intraperitoneal route would be expected to be more efficient for eliciting potent B-cell and T-cell responses. Such systemic vaccination with Listeria vectors may also readily provide access to dendritic cells for eliciting robust immune responses (28). It is noteworthy that subcutaneous injection delivering r-Listeria ⌬actA prfA* does not elicit humoral and cellular immune responses as efficiently as intravenous or intraperitoneal vaccinations.…”
Section: Discussionmentioning
confidence: 99%